Adjuvant Use of Rifampin for Refractory Intrahepatic Cholestasis of Pregnancy. Issue 3 (September 2018) - Liu, James; Murray, Amanda M.; Mankus, Erin B.; Ireland, Kayla E.; Acosta, Ometeotl M.; Ramsey, Patrick S.
Abstract : BACKGROUND: Intrahepatic cholestasis of pregnancy is an incompletely understood disease that poses significant fetal risks, including stillbirth. Treatment of intrahepatic cholestasis of pregnancy is aimed at relieving maternal symptoms and improving fetal outcomes. CASE: A 21-year-old gravid woman, 3 para 0111, presented at 27 2/7 weeks of gestation with severe intrahepatic cholestasis of pregnancy. Her clinical course was refractory to first-line therapy with ursodiol, and she was started on rifampin with rapid improvement of symptoms and transaminitis. Despite maternal improvement, she was delivered at 31 weeks of gestation for persistent nonreassuring fetal status. CONCLUSION: Rifampin may be an effective adjunctive therapy for intrahepatic cholestasis of pregnancy refractory to ursodiol alone. Additional research is needed to assess short-term and long-term maternal and newborn outcomes, because fetal deterioration still occurred in spite of maternal improvement. Abstract : Rifampin may be an effective adjunctive therapy for intrahepatic cholestasis of pregnancy refractory to ursodiol alone.